COMPARISON OF ESCHERICHIA COLI CONCENTRATION BETWEEN BENGKALIS COASTAL WATERS AND ESTUARY BANTAN TENGAH RIVER - Nursyirwani .; B.A. Moestomo (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Bengkalis coastal waters and estuary Bantan Tengah River have been evaluated for bacteriological pollution level from November 2000 to April 2001. The objective was to compare Escherichia coli concentration as an indicator organism in the two ecosystems. The results indicated that E. coli concentration was higher in Bengkalis coastal waters than at estuary Bantan Tengah River, either at spring or at ebb tides. E. coli concentration, in Bengkalis coastal waters was higher at spring tide (993 cfu/100 ml) than that at ebb tide (775 cfu/100 ml). On the contrary, the E. coli concentration in estuary Bantan Tengah River was higher at ebb tide (247 cfu/100 ml) than at spring tide (22 cfu/100 ml).